Indirect treatment comparison of abatacept with methotrexate versus other biologic agents for active rheumatoid arthritis despite methotrexate therapy in the United kingdom. - Guyot, P; Taylor, P; Christensen, R; Pericleous, L; Drost, P; Eijgelshoven, I; Bergman, G; Lebmeier, M (2012)
OBJECTIVE: To compare the efficacy of abatacept and alternative biologic disease-modifying antirheumatic drugs (DMARD) in patients with rheumatoid arthritis (RA) and an inadequate response to methotrexate (MTX) in the United Kingdom. METHODS: A systematic literature search identified 11 individual studies investigating the efficacy of abatacept, infliximab, adalimumab, etanercept, certolizumab pegol, and golimumab in adult patients with RA that did not respond to MTX. The clinical trials included in this analysis were similar in trial design, baseline patient characteristics, and background therapy (i.e., MTX). The key clinical endpoints of interest were the Health Assessment Questionnaire (HAQ) change from baseline (CFB) and the American College of Rheumatology (ACR) responses at 6 months (24-28 weeks). Results were analyzed using Bayesian network metaanalysis methods, and were expressed as differences in HAQ CFB and ACR20/50/70 relative risks, with 95% credible limits (CrL). RESULTS: Analysis of HAQ CFB at 6 months showed that abatacept is more efficacious than placebo [mean difference in HAQ CFB: -0.30 (95% CrL -0.42; -0.16)] and comparable to all other biologic agents, in patients receiving MTX as background treatment. Abatacept is also expected to result in a higher proportion of ACR responders compared to placebo, with relative risks ranging from 1.90 (95% CrL 1.24; 2.57) for ACR20 to 3.72 (95% CrL 1.50; 10.52) for ACR70, and to result in comparable proportions of ACR responders as other biologic agents, at 6 months. CONCLUSION: Abatacept is expected to result in improvement in functional status comparable to other recommended biologic agents in patients with RA who are unresponsive to MTX in the UK.